Metabolite Profiling of Eleutherine palmifolia (L.) Merr. By HPTLC-Densitometry and its Correlation with Anticancer Activities and In Vitro Toxicity - Mutiah, Roihatul; Hadya, Chorida Muhjatul; Ma'arif Z.A, Burhan; Bhagawan, Weka Sidha; Annisa, Rahmi; Indrawijaya, Yen Yen Ari; Huwaida, Fadhila Isma; Ramadhani D.A., Ria; Susilowati, Retno; Taufik, Imam (Indonesian Journal of Pharmacy, 2019)
Eleutherine palmifolia (L.) Merr. (E. palmifolia) is a plant that used as raw material for herbal medicines. The difference of growing location the medicinal plants affects the difference of metabolite content, It also affects the pharmacological activity and toxicity of the plant. This study aims to determine the profile of metabolites (metabolite fingerprinting), anticancer profiles, toxicity/safety profiles from several different regions in Indonesia for the purpose of authentication, efficacy, safety and quality control of these plants. Samples were sampled from 6 different locations in Indonesia, they were West Java, Central Java, East Java, East Borneo, Central Borneo, and South Borneo. Metabolite fingerprinting was determined by HPTLC-densitometry method, the profile of anticancer activity and toxicity was known by the MTT-ELISA method. The difference between metabolite fingerprinting, anticancer profile, toxicity/safety profile was analyzed by Principal Component Analysis (PCA) and Hierarchical Component Analysis (HCA). Whereas the relation between metabolite fingerprinting, anticancer profile, toxicity/safety profile was analyzed by Partial Least Square (PLS). The results of the metabolite profile analysis with PCA showed that E. palmifolia from 6 different locations gave different metabolite profiles and there were 3 metabolites that had a significant effect on cluster formation. samples are Rf 055, 059, and 044. The results of the HCA analysis showed that the 6 regions are in one cluster the same one. The analysis of PLS-DA showed that the metabolites for anticancer activity are found in Rf 059, 076, 093 and Rf 034. While the metabolites for toxicity are Rf 002, Rf 044 and Rf 059.